Theological Study of The Belis Culture in Marriage of The West Sumba Community, Tana Righu District - Nadap Rafi Ghungnga; Eki Neonisa; Maya Djawa (International Perspectives in Christian Education and Philosophy, 2025)
This study examines theologically the practice of giving dowry in Sumbanese weddings. This tradition has been passed down from generation to generation and is often associated with church weddings. Various responses to dowry, especially from Christians, are the main focus. The method used is a literature study, with the object of study being the giving of dowry in the marriages of biblical figures such as Isaac and Rebekah, Jacob and Rachel, David and Michal, and Shechem and Dinah. The theological reflections produced include: First, dowry in the Bible functions as a sign of appreciation for women and their families. Second, dowry is not coercion, but rather a way for men to show love for their future wives. Thus, dowry in Sumbanese culture does not conflict with Christian faith and has a positive value for helping each other. The implications include: First, dowry must be in accordance with the man's ability. Second, dowry should not be used as a tool to fulfill personal ambitions. Payment of dowry should be for the common good. Third, dowry must be given in an honorable manner, without justifying any means to prove the ability to pay dowry at a high price.